The impact of place attachment on the environmentally responsible behavior of residents in National Park gateway communities and the mediating effect of environmental commitment: a case of China National Park - Xie, Xiangxiang; Wang, Zenong (Frontiers in Psychology, 2024)
As a member of the national park, the environmentally responsible behavior of the entrance community residents has an important impact on the ecological protection of the national park.However, there are still insufficient studies on the mechanism of influence of community residents' place attachment on environmentally responsible behavior and the role of environmental commitment.Based on the theory of interdependence, this study explored the impact of residents' place attachment in a national park gateway community on environmentally responsible behavior, and examined the mediating role of environmental commitment. We conducted empirical research on Shuiman gateway community of the Hainan Tropical Rainforest China National Park. Through structural equation modeling, the survey of 375 residents yielded the following conclusions: (1) place dependence indirectly affect environmentally responsible behavior via the mediating effect of place identity; (2) both place dependence and place identity have a positive and significant impact on environmental commitment; (3) environmental commitment has a positive and significant impact on environmentally responsible behavior; (4) the mediating effect of environmental commitment on the impact of place dependence on environmentally responsible behavior is significant and "place identity-environmental commitment" also has a significant mediating effect. Finally, three managerial insights were discussed. This study enriches the connotation and application scope of interdependence theory, explains the different roles of place dependence, place identity, and environmental commitment in the study of environmentally responsible behavior, and provides some inspiration for future research and practice of environmentally responsible behavior. It is helpful for community residents to participate in the ecological environment governance of national parks and achieve sustainable development.